Turning science into sense - M'boob, Sulayman (Technical Centre for Agricultural and Rural Cooperation, 1996)
Dr Sulayman M'boob is Senior Crop Protection Officer at the FAO Regional Office for Africa in Accra, Ghana. He is responsible for FAO's Plant Protection programme in the Africa region. Previously, he was Director of the Crop Protection Services...